2022
DOI: 10.1186/s40168-022-01247-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome signatures linked to HIV-1 reservoir size and viremia control

Abstract: Background The potential role of the gut microbiome as a predictor of immune-mediated HIV-1 control in the absence of antiretroviral therapy (ART) is still unknown. In the BCN02 clinical trial, which combined the MVA.HIVconsv immunogen with the latency-reversing agent romidepsin in early-ART treated HIV-1 infected individuals, 23% (3/13) of participants showed sustained low-levels of plasma viremia during 32 weeks of a monitored ART pause (MAP). Here, we present a multi-omics analysis to identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…These connections begin to be evident during viruses’ general defense, invasion, and replication phases [ 60 , 61 ]. In fact, reviewing the existing literature on HIV [ 62 , 63 , 64 , 65 , 66 , 67 ] and poliovirus [ 68 ], other RNA viruses also appear to have significant involvement in the gut microbiome. In fact, a recent study observed HIV gene sequences in bacteria isolated from the oropharyngeal tract of Kenyan children [ 63 ], and this finding is synergic with the diatribe of the bacterial cofactor in HIV and its connection with mycoplasmas [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…These connections begin to be evident during viruses’ general defense, invasion, and replication phases [ 60 , 61 ]. In fact, reviewing the existing literature on HIV [ 62 , 63 , 64 , 65 , 66 , 67 ] and poliovirus [ 68 ], other RNA viruses also appear to have significant involvement in the gut microbiome. In fact, a recent study observed HIV gene sequences in bacteria isolated from the oropharyngeal tract of Kenyan children [ 63 ], and this finding is synergic with the diatribe of the bacterial cofactor in HIV and its connection with mycoplasmas [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection is also associated with decreased abundance, composition, and diversity of gut microbiota. These changes in turn contribute to persistent inflammation and microbial translocation, dysfunctional metabolism of the host, and HIV disease progression and reservoir size [ 26 , 27 , 28 , 29 , 30 ]. Importantly, antiretroviral therapy does not fully restore the integrity of the gut epithelial barrier and the disrupted gut microbiota that result from HIV infection despite its potent suppressive effects on HIV replication [ 27 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported inconsistent results. In humans, the administration of oral typhoid or an intranodal and intramuscularly human immunodeficiency virus (HIV)-1 vaccine was not reported to significantly affect the composition of the intestinal microbiota one week to several months after vaccination 12 , 21 , 22 . The first two studies used amplicon sequencing, while the third used shotgun metagenomic sequencing.…”
mentioning
confidence: 99%
“…Only a few studies have investigated whether the administration of vaccines is associated with changes in the composition of the intestinal microbiota 12,[20][21][22][23][24][25][26] , and whether the changes induced by vaccination, in turn, influence vaccine immunogenicity 20 . These studies have reported inconsistent results.…”
mentioning
confidence: 99%